What happened to you? ebook Conversations on trauma, resilience, and healing. - Winfrey, Oprah (2021)
ONE MILLION COPIES SOLD #1 NEW YORK TIMES BESTSELLER Our earliest experiences shape our lives far down the road, and What Happened to You? provides powerful scientific and emotional insights into the behavioral patterns so many of us struggle to understand. "Through this lens we can build a renewed sense of personal self-worth and ultimately recalibrate our responses to circumstances, situations, and relationships. It is, in other words, the key to reshaping our very lives." —Oprah Winfrey This book is going to change the way you see your life. Have you ever wondered "Why did I do that?" or "Why can't I just control my behavior?" Others may judge our reactions and think, "What's wrong with that person?" When questioning our emotions, it's easy to place the blame on ourselves; holding ourselves and those around us to an impossible standard. It's time we started asking a different question. Through deeply personal conversations, Oprah Winfrey and renowned brain and trauma expert Dr. Bruce Perry offer a groundbreaking and profound shift from asking "What's wrong with you?" to "What happened to you?" Here, Winfrey shares stories from her own past, understanding through experience the vulnerability that comes from facing trauma and adversity at a young age. In conversation throughout the book, she and Dr. Perry focus on understanding people, behavior, and ourselves. It's a subtle but profound shift in our approach to trauma, and it's one that allows us to understand our pasts in order to clear a path to our future—opening the door to resilience and healing in a proven, powerful way.